Survey of Ice Problem Areas in Navigable Waterways. - Zufelt,J; Calkins,D (1985)
This report presents the findings of a survey of ice problems encountered on the nation's major navigable waterways. A survey questionnaire was developed and, through a field review group, was distributed to lock and dam facilities on the Allegheny, Monongahela, Ohio, Kanawha, Kaskaskia, and Mississippi Rivers and the Illinois Waterway. Analysis of the completed questionnaires identified 13 ice problem categories. The report describes each category of ice problem encountered, as well as the cited methods, operational and/or structural, undertaken to reduce the impact of each ice problem. Originator supplied keywords: Ice control, Ice problems, Lock and dam facilities, Questionnaire survey, River Ice Management (RIM) program, Winter navigation.